Impact of Intimate Partner Violence on Iranian Children’s Growth and Development: A Descriptive-analytical Study - Munn-Sann Lye; Mehran Zarghami; amshid Yazdani Charati; Fatemeh Abdollahi (Oman Medical Journal, 2023)
Objectives: This study aimed to determine the prevalence of different types of intimate partner violence (IPV) experienced by married Iranian women and their impact on the growth and development of their children. Methods: For this descriptive-analytical study, we recruited the mothers of one-year-old children attending primary health centers in Gonbad-e-Kavoos city, Iran. The data was collected using a questionnaire comprising the World Health Organization Domestic Violence, Ages and Stages Questionnaire-12; and queries related to the participants’ socio-economic, obstetrics, demographic, and anthropometric characteristics. The body mass index z (BMI z) scores of the children were divided into five categories based on the World Health Organization’s classification: severely underweight (z < -3), underweight (-3 ≤ z < -2), normal (-2 ≤ z < 1), overweight (1 ≤ z ≤ 2), and obese (z > 2). The data were subjected to descriptive analysis, chi-square test, and regression. Results: A total of 596 of mother-child dyads were included in this study. The prevalence of psychological, physical, and sexual IPV was 29.5%, 7.4%, and 2.4%, respectively. Most children (91.7%) had normal weight while the rest were overweight or obese. Developmental problems were reported in 1.7% of children. The education level of the father was significantly related to IPV (p =0.001) while the type of his occupation was related to delay in child growth (p =0.020). There was no significant difference between BMI z-score and developmental disabilities in the children of women exposed and not exposed to any type of IPV. Conclusions: The prevalence of psychological IPV was high while those of physical and sexual IPV were low. The rates of poor child growth and development were also low. The father’s educational and socio-economic status influenced IPV and the children’s growth deficits.